Internet and Literature and Versai (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is devoted to the study of the role and place of the Internet space in the modern literary community, in particular, on the example of the work of the young Russian writer A. Ganieva.